Middle Eastern security, the US pivot and the rise of ISIS - Dodge, Toby; Hokayem, Emile (Adelphi (Series) (International Institute for Strategic Studies), 2014)
To mark the tenth anniversary of the IISS Manama Dialogue process and to capitalise on the new light it has shed on security issues in the Gulf and the wider Middle East, this Adelphi brings together the results of two workshops held by IISS in its Middle East office in Manama. Featuring essays by nine IISS analysts and a number of outside experts, the book examines the most important geostrategic issues in the region, including the myriad security challenges it faces. These interlinked papers focus in particular on the regional ramifications of the civil war in Syria and the effects of the United States changing posture in the Middle East. The aim of this Adelphi is to both highlight and develop the ongoing discussions and debates about Gulf security that have taken place in the Manama Dialogue over the previous decade, and that will continue to do so over the next ten years. As such, it capitalises on the IISS's global reputation not only as the world leader in convening para-diplomatic events, but also as a provider of the best possible objective information and analysis on global military and political developments.